Synthesis, Anti‐inflammatory, and Arginase Inhibitory Activity of Piceatannol and Its Analogs. (17th February 2017) - Moon, Insu; Damodar, Kongara; Kim, Jin‐Kyung; Ryoo, Sungwoo; Jun, Jong‐Gab
Abstract : The present study describes the synthesis of piceatannol (2 ) and its analogs (3–8 ) using Wittig‐Horner reaction, Colvin rearrangement, and Sonogashira reaction as key steps and also evaluation of their inhibitory potency on the production of inflammatory mediator nitric oxide (NO) in lipopolysaccharide (LPS)‐induced RAW‐264.7 macrophages. Three compounds7 (90.1%), 8 (60.8%), and6 (55.2%) were found to potently inhibit NO production induced by LPS without affecting the viability of RAW‐264.7 cells. In addition, their Arginase I and II inhibition activity was also evaluated. In this study, three compounds, i.e., compounds2–4 were showed good inhibition activity to both arginase I and II. Of the synthesized compounds, compound2 exhibited maximum inhibitory activity of 28% (arginase I) and 26% (arginase II) at 10 μM concentration followed by compounds3 and4 of 20 and 22% to arginase I, 22 and 23% to arginase II, respectively. Abstract :